2018
DOI: 10.17576/jkmjc-2018-3403-11
|View full text |Cite
|
Sign up to set email alerts
|

Youth Offline Political Participation: Trends and Role of Social Media

Abstract: Recently, the growing body of research has waded into the decline of formal political participation and engagement among youth especially voting and party allegiance due to the heightened youth activism such as protests and demonstrations. However, past research proposes that there is a significant relationship between the usage of social media and online political participation among youth. Many of those studies have inordinately relied on college students as samples rather than the entire population of youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(34 reference statements)
0
9
1
2
Order By: Relevance
“…Moreover, some authors even mention specific cases of using the Internet to control the attitude and behavior of young people. For example, recent studies show that the Internet and social media can be a very useful resource for civic education [3] and for popularization of a healthy lifestyle among young people [4]. So, perhaps, we can say that in fact there is nothing strange or unusual in the fact that Russian youth is very active in using the Internet.…”
Section: The First``digital Natives'' Of Russian Societymentioning
confidence: 99%
“…Moreover, some authors even mention specific cases of using the Internet to control the attitude and behavior of young people. For example, recent studies show that the Internet and social media can be a very useful resource for civic education [3] and for popularization of a healthy lifestyle among young people [4]. So, perhaps, we can say that in fact there is nothing strange or unusual in the fact that Russian youth is very active in using the Internet.…”
Section: The First``digital Natives'' Of Russian Societymentioning
confidence: 99%
“…Previous research has found that young people's political impulses are channelled into various forms of political participation, such as traditional (offline) (Mohamad, 2018) or the internet (online) (Kahne & Bowyer, 2018). However, this tendency is inconsistent, mainly traditional or offline political participation such as voting during elections (General Election or By-Election), campaigning and membership of political party organizations (Rogstad & Vestel, 2011).…”
Section: Political Participation Of Young People In Social Mediamentioning
confidence: 99%
“…Moreover, some authors even mention specific cases of using the Internet for management of young people's attitudes and behaviour. For example, recent researches show, that the Internet and social media can be a very useful resource for civic education [10] and for popularization of healthy lifestyle among youth [6]. So, perhaps we can say, that there is nothing strange or unusual in fact, that Russian youth tends to use the Internet very actively.…”
Section: Literature Reviewmentioning
confidence: 99%